Responsible Business in Uncertain Times and for a Sustainable Future - Capaldi, Nicholas; Idowu, Samuel O.; Schmidpeter, René; Brueckner, Martin (CSR, Sustainability, Ethics & Governance, 2019)
XXII, 223 p. 29 illus., 2 illus. in color.